Analisis Kebutuhan terhadap Aplikasi “Warkop-Peduli Covid” Pada Warkop Tarakan Brewing House - Haikal Haikal; Imaniar Sevtiyani (Universitas Pekalongan, 2020)
Coffee shop has become a public space that provides freedom for visitors to engage in chatting, gathering and seeking information. The gathering activity that occurs can be a risk for Covid-19 transmission. The purpose to analyze the system that has been running and its weaknesses, to analyze the needs and the proposed system related to the application